Analysis of the topographic effect on the radiometric correction of MERIS images - G. Grau (Revista de Teledetección, 2014)
Topography alters the vertical structure of the atmosphere and, therefore, its radiative properties regarding the reflection and transmission of the solar radiation. Also it modifies the conditions of illumination of terrain, with remarkable influence in the remote sensing measures of the terrestrial surface in the optical spectrum. In this work we have applied two models of atmospheric and radiometric correction on an ENVISAT/MERIS image, considering the topography, to analyse the importance of such effects. For this, we have exploited the recent rise of Digital Models of Elevation (MDE) sufficiently detailed and precise, available to a global scale, that open new prospects for the topographical corrections of remote sensing data. The results show the adjustment of the conjoint correction model (atmospheric and topographical) in the considered case, improving comparison of spectral signatures of similar surfaces independently of the elevation or the conditions of illumination, compensating the relative variations caused by the topography in the reflectivity measured by sensors. Although the remote sensing of the terrestrial surface has tended traditionally to avoid the bands of atmospheric absorption, a peculiarity that presents the ENVISAT/MERIS images is the availability of a band (O2A) of absorption of the oxygen, located in the 761.5 nm. This band is used mainly for atmospheric corrections (estimate of the surface’s pressure, elevation of clouds, aerosols effects, etc.). But also it has been employed recently to determine the fluorescence of the vegetation, consequently this band of absorption has received remarkable attention in the last years. Considering that this absorption of the oxygen is strongly affected for topography, the determination of information on the terrestrial surface from this absorption of the oxygen requires a very precise correction of the topographical effects. Therefore in this work we analyse in particular the effect of the peak of reflectivity at 761.5 nm originated by an inappropriate correction of the topography and we study the existent relationship between the local atmospheric pressure and the depth band of absorption of the oxygen in this wavelength.